2019
DOI: 10.4314/mmj.v31i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictors of adherence and retention for antiretroviral therapy among HIV-positive adults in Enugu, Nigeria

Abstract: BackgroundHIV infection and AIDS are majorpublic health challenges in Nigeria, a country with one of the highest rates of new infection in sub-Saharan Africa and the second largest HIV epidemic in the world.Non-adherence to medication and defaulting from treatment are the two major challenges faced by anti-retroviral therapy (ART) programs in resource-constrained settings. This study was undertaken to determine the rate and predictors of adherence to medication and retention among people living with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
1
12
0
2
Order By: Relevance
“…Optimal viral load suppression (VLS) is critical in reducing morbidity and mortality associated with HIV and its associated opportunistic infections as well as minimizing the likelihood of HIV transmission to uninfected people [2][3][4][5]. Despite these benefits, challenges still exist and some patients receiving antiretroviral (ARV) therapy fail to achieve optimal viral suppression [6][7][8]. In order to achieve these UNAIDS targets, unbiased populationbased data on the determinants of VLS are needed to inform targeted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal viral load suppression (VLS) is critical in reducing morbidity and mortality associated with HIV and its associated opportunistic infections as well as minimizing the likelihood of HIV transmission to uninfected people [2][3][4][5]. Despite these benefits, challenges still exist and some patients receiving antiretroviral (ARV) therapy fail to achieve optimal viral suppression [6][7][8]. In order to achieve these UNAIDS targets, unbiased populationbased data on the determinants of VLS are needed to inform targeted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Retention in care is still a significant challenge in the HIV treatment cascade and varies extensively across regions, leading to poor adherence to ART 11 12. Several factors across different socioecological levels, such as environmental and health-level factors, serve as barriers to ART adherence 5 6 13. In Nigeria and elsewhere, poor socioeconomic status, stigma, pill burden, poor support and distance to ART clinics have been identified as barriers to ART adherence 14–16…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, place of residence has not been examined in numerous ART adherence-related studies in Nigeria 25–27. Nevertheless, the association between place of residence and ART adherence is not linear; while some studies have found an association after multivariate analysis,13 28 others did not 29 30. A meta-analysis conducted by Fite24 shows that PLWH residing in Ethiopia’s urban areas were twofold more likely to adhere to ART than those in rural areas 24.…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons for not complying with ARV therapy are being busy and forgetting. 9,10 Other factors that influence adherence to take ARVs are age, sex, knowledge, education level, ethnicity, type of occupation, duration of ARV therapy, illiteracy, depression, patient acceptance of his condition, improvement of health status after ARV therapy, motivation, alcohol consumption, drug use, family support, travel time to the hospital for more than 1 hour, availability of drugs, difficulty in remembering drug dosages, staff attitudes towards patients, and a good relationship between patients and health professionals. [9][10][11][12][13][14][15][16][17][18][19][20] Most studies examining factors associated with ART retention have been undertaken in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Other factors that influence adherence to take ARVs are age, sex, knowledge, education level, ethnicity, type of occupation, duration of ARV therapy, illiteracy, depression, patient acceptance of his condition, improvement of health status after ARV therapy, motivation, alcohol consumption, drug use, family support, travel time to the hospital for more than 1 hour, availability of drugs, difficulty in remembering drug dosages, staff attitudes towards patients, and a good relationship between patients and health professionals. [9][10][11][12][13][14][15][16][17][18][19][20] Most studies examining factors associated with ART retention have been undertaken in Western countries. Even though HIV incidence in Indonesia is high and continues to increase and levels of ART retention are very low, there are still very few studies on ARV therapy adherence to PLWHA who access ARV services in private clinics in Indonesia, especially in MSM groups.…”
Section: Introductionmentioning
confidence: 99%